Serum cystatin C and stroke risk: a national cohort and Mendelian randomization study - Qi, Yitian; Shang, Xinyun; Han, Tianjiao; Han, Ning; Jiang, Ziwei; Yan, Han; Yue, Siqi; Sun, Qichao; Liu, Lin; Cui, Cancan (Frontiers in Endocrinology, 2024)
The debate over the causal and longitudinal association between cystatin C and stroke in older adults persists. Our aim was to assess the link between cystatin C levels, both measured and genetically predicted, and stroke risk.This study employed a retrospective cohort design using samples of the China Health and Retirement Longitudinal Study (CHARLS), which is a nationally representative cohort recruiting individuals aged 45 years or above. Multivariate logistic model and two-sample Mendelian randomization framework were conducted to investigate the longitudinal and genetically predicted effect of serum cystatin C on stroke.The study population had a mean age of 59.6(SD ±9.5), with 2996(46.1%) females. After adjusting for confounding factors, compared to those in the first quartile of cystatin C, those in the last quartile had the greatest risk of stroke incidence (OR, 1.380;95% CI, 1.046-1.825). The Mendelian randomization analysis showed that a genetically predicted cystatin C level was positively associated with total stroke (OR by inverse variance weighted method, 1.114; 95% CI, 1. 041-1.192).This national cohort study suggests that higher serum cystatin C is associated with an increased risk of total stroke, which is further supported using Mendelian randomization.